A study to compare digital technique and suction catheter guided technique for insertion of proseal laryngeal mask airway in children - Teena Bansal; Somesh Sharma; Himani Mittal (Wolters Kluwer Medknow Publications, 2018)
Objectives: The present study was conducted to compare digital technique and suction catheter guided technique for Proseal laryngeal mask airway insertion regarding ease of insertion, number of attempts for successful insertion and insertion time in children. Methods: This prospective randomised study included one hundred children of age 1-12 years divided into two groups. In group I, Proseal laryngeal mask airway insertion was inserted using digital technique and in group II, suction catheter guided technique was used for insertion. Results: In group I, Proseal laryngeal mask airway insertion was successfully inserted in 45 patients (90%), while in group II, insertion was successful in 49 patients (98%). Insertion was successful in 37 patients (74%) in first attempt and 8 patients (16%) required 2nd attempt in group I, whereas in group II, 1st attempt was successful in 47 patients (94%) and 2nd attempt was required in 2 patients (4%). Proseal laryngeal mask airway insertion failed in 5 patients (10%) in group I while it failed in only 1 patient (2%) in group II. Mean insertion time was 23.88 ± 2.58 sec in group I, whereas in group II, time was 19.34 ± 1.81 sec (p=0.001), the difference being statistically significant. Conclusion: Suction catheter guided technique is easier and more successful as compared to digital technique in children. It is less traumatic and insertion time is also less with this technique.